2021
DOI: 10.1108/jamr-04-2021-0143
|View full text |Cite
|
Sign up to set email alerts
|

Food supply chain management (FSCM): a structured literature review and future research agenda

Abstract: PurposeThe main purpose of this paper is to conduct a review of the literature published on food supply chain management (FSCM) in last one and half decade to find out the ongoing research in the field, identify gaps and develop relevant research questions (RQs) from the perspectives of academicians, researchers, policymakers and corporate for the future research.Design/methodology/approachIn all 281 research articles published on FSCM between the years 2005 and 2020 used for searching online databases such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…There are twelve European suppliers, who receive their products from global producers. These suppliers supply a central distribution center (DC) in Germany, which in turn supplies five In 2021, Patidar et al [22] conducted a structured review of the literature published on FSC management in the past 15 years to give an overview of the research field and identify research gaps. Among other implications, the authors found that even though a large number of articles discussed and highlighted the problems, challenges, and issues in the FSC, few studies presented strategies to overcome them.…”
Section: A Case Study In Organic Food Supply Chainsmentioning
confidence: 99%
“…There are twelve European suppliers, who receive their products from global producers. These suppliers supply a central distribution center (DC) in Germany, which in turn supplies five In 2021, Patidar et al [22] conducted a structured review of the literature published on FSC management in the past 15 years to give an overview of the research field and identify research gaps. Among other implications, the authors found that even though a large number of articles discussed and highlighted the problems, challenges, and issues in the FSC, few studies presented strategies to overcome them.…”
Section: A Case Study In Organic Food Supply Chainsmentioning
confidence: 99%
“…To maintain this momentum, food supply chain has to be revamped in order to match this pace. The food supply chain is complex with perishable goods and several small stakeholders [ 13 ]. Many researchers have noteworthy contributions in this domain field, but still, there are gaps in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Research in the field of food supply chain management (FSCM) has gained momentum in the 15 years. However, compared to other FSCM sub-areas, few authors have addressed issues and challenges related to agri-food supply chains in developing countries (Patidar et al, 2022). Moreover, the agri-food area is very specific.…”
Section: Introductionmentioning
confidence: 99%